PENGEMBANGAN KETERAMPILAN SISWA LKP PRISMA PROFESIONAL UNTUK DUNIA KERJA MELALUI PELATIHAN FOLDING NAPKIN - Nugroho, Truli; Prakoso, Yusak; Adinugroho, Suryo; Mulyomo, Andreas Aris Eko (Jurnal Pengabdian Bukit Pengharapan, 2024)
The aim of this community service is to provide students with additional knowledge in the field of Food Beverage Servive (Folding Napkin) at the Prisma Professional LKP in Surabaya City. The target is also female students training at LKP Prisma Professional in all skill fields. This activity will really help students to further develop their knowledge and skills, especially in the field of Food Beverage Service (Folding Napkin). The skill of folding napkins is an important technique in restaurant and hospitality services that plays a role in the aesthetics of presentation. Through this community service activity, LKP Prisma Professional organizes napkin folding training aimed at the general public and workers in the hospitality sector. The aim of this service is to provide practical skills that can improve the work competence of the participants. The teaching methods used include participatory approaches and direct practice. The results of this training show an increase in the participants' skills, which can then be applied in the world of work or business in the hotel and food services sector.